Reconstructing public housing : Liverpool's hidden history of collective alternatives - Thompson, Matthew (Liverpool University Press, 2020)
Reconstructing Public Housing tells the story of Liverpool's 'cooperative revolution' in municipal housing development in the 1970s, how this laid the foundations for the first ever architectural or urban regeneration project to win the artworld's coveted Turner Prize, and what this says about how we might renew public housing, collectively.